Asymptomatic Bacteremia in Children Infected with Human Immunodeficiency Virus in Calabar, South-South, Nigeria - Ochigbo, Sunday O.; Ikpeme, Offiong E.; Ewa, Atana U.; Happiness, Ntia A. (International Journal of Child Health and Nutrition, 2015)
Background: Asymptomatic Human Immunodeficiency Virus (HIV) infected children are prone to serious bacterial infection as a result of poor immunity. Objective: This was to determine the common pathogenic organisms responsible for bacteremia among asymptomatic HIV infected children attending the outpatient clinics at the University of Calabar Teaching Hospital, Nigeria. Subjects and Methods: This prospective non randomized cross-sectional study was conducted over 6months from January 1st to 30th June 2014 among cohorts of HIV infected Anti-retroviral (ARV) naive and experienced children attending the clinic. Ethical approval was obtained from the ethical committee of the institution. Blood culture specimens were collected from all HIV infected patients who met the criteria for enrollment. All specimens with isolated bacteria organisms were treated with antibiotics according to the sensitivity pattern, in addition to administered Anti-retroviral drugs. Results: Out of the total of 109 patients recruited, 38(34.9%) had bacteremia. There were more males (57.9%), and most of them (63.2%) had Highly Active Anti-Retroviral Therapy (HAART) for more than 24weeks. Bacteremia was inversely proportional to the CD4 count. The commonest organism isolated was unclassified Coliforms (47.3%) followed by Staphyloccocus aureus (39.5%). Conclusions: HIV infected children are prone to bacteremia especially among those with low CD4 count. Coliform was the commonest organism isolated. We recommend that HIV infected children be routinely investigated for bacteremia.